Depression and Human Immunodeficiency Virus Infection Are Risk Factors for Incident Heart Failure Among Veterans: Veterans Aging Cohort Study. Issue 17 (27th October 2015) - White, Jessica R.; Chang, Chung-Chou H.; So-Armah, Kaku A.; Stewart, Jesse C.; Gupta, Samir K.; Butt, Adeel A.; Gibert, Cynthia L.; Rimland, David; Rodriguez-Barradas, Maria C.; Leaf, David A.; Bedimo, Roger J.; Gottdiener, John S.; et al.
Abstract : Background—: Both HIV and depression are associated with increased heart failure (HF) risk. Depression, a common comorbidity, may further increase the risk of HF among adults with HIV infection (HIV+). We assessed the association between HIV, depression, and incident HF. Methods and Results—: Veterans Aging Cohort Study (VACS) participants free from cardiovascular disease at baseline (n=81 427: 26 908 HIV+, 54 519 without HIV [HIV−]) were categorized into 4 groups: HIV− without major depressive disorder (MDD) [reference], HIV− with MDD, HIV+ without MDD, and HIV+ with MDD. International Classification of Diseases, Ninth Revision codes from medical records were used to determine MDD and the primary outcome, HF. After 5.8 years of follow-up, HF rates per 1000 person-years were highest among HIV+ participants with MDD (9.32; 95% confidence interval [CI], 8.20–10.6). In Cox proportional hazards models, HIV+ participants with MDD had a significantly higher risk of HF (adjusted hazard ratio, 1.68; 95% CI, 1.45–1.95) compared with HIV− participants without MDD. MDD was associated with HF in separate fully adjusted models for HIV− and HIV+ participants (adjusted hazard ratio, 1.21; 95% CI, 1.06–1.37; and adjusted hazard ratio, 1.29; 95% CI, 1.11–1.51, respectively). Among those with MDD, baseline antidepressant use was associated with lower risk of incident HF events (adjusted hazard ratio, 0.76; 95% CI, 0.58–0.99). Conclusions—: Our study is the first to suggest that MDD is an independent risk factor for HF in HIV+ adults. These results reinforce the importance of identifying and managing MDD among HIV+ patients. Future studies must clarify mechanisms linking HIV, MDD, antidepressants, and HF and identify interventions to reduce HF morbidity and mortality in those with both HIV and MDD. Abstract : Supplemental Digital Content is available in the text.